Reverberation time improvement of lecture auditorium: A case study. (January 2018) - Yadav, Saurabh; Sharma, Gaurav; Nag, Sarthak; Gupta, Arpan
In this study, reverberation time of a lecture auditorium has been analyzed experimentally and analytically. It is well-known fact that reverberation time affects the speech intelligibility and hence should be within the range of possible optimum values. Experiments were performed to calculate the reverberation time of a lecture auditorium constructed at Indian Institute of Technology Mandi (IIT Mandi), for different internal conditions such as furniture and curtains. Experimental results were compared with the theoretically calculated values of reverberation time. It is found that acoustic performance of the lecture auditorium has significantly improved using curtains on the windows and furniture. For further improvement, it has also been suggested to use the carpet on the floor of the auditorium. The theoretical value of reverberation time is also calculated to show the improvement which can be achieved using carpet. The effect of audience on reverberation time has also been studied theoretically.